Mt Darwin AICs: continuity or discontinuity with biblical pre canonical prophets - Pirirani, Richard (Midlands State University, 2017)
This thesis critically examines and compares the prophetic activities of AIC and modus operandi of AIC prophets with the pre canonical biblical prophets. There have been constant criticisms among Zimbabweans, both Christians and non-Christians about the prophetic activities and mode of operation of AIC prophets although the research is limited to Mt Darwin. The research is limited to Mt Darwin area because has the finger tip knowledge of the churches under discussion and a resident of the area. The misunderstanding and the misconceptions in the mode of operation of some AIC in Zimbabwe have called for a study of the kind of analysing the prophetic activities and modus operandi of these prophets. Besides examining the prophetic activities and modus operandi of prophets in Mt Darwin Area, the thesis will also compare their operation with that of biblical prophets to find out the similarities and dissimilarities. The primary data for this study were obtained through interviews. The researcher visited some shrines of the churches selected in Mt Darwin area and interviewed prophets, leaders and members of the churches. Secondary data were obtained through relevant literatures. The researcher read some books and articles on the topic. The study revealed that the A prophets in Mt Darwin area are African Traditional fundamentalists and as such biblical prophets are seen to have adopted some concepts from other cultures and religions like that of the Canaanites and the Egyptians. Many AIC prophets are found tapping into African Traditional Religion in their activities and mode of operation